Assessing resilience and sensitivity patterns for fish and phytoplankton in French lakes - Barbbara Silva Rocha; Maxime Logez; Aurélien Jamoneau; Christine Argillier (Global Ecology and Conservation, 2023)
Ecosystem vulnerability is crucial information for conservation managers. We assessed the sensitivity and resilience (vulnerability components) patterns of fish and phytoplankton assemblages in French lakes (natural and artificial). We measured resilience (functional redundancy) and sensitivity, an index considering three characteristics of rarity for species. We hypothesized that geographically close lakes have similar resilience and sensitivity for fish assemblages (H1). Then, we tested the correlation between environmental gradients and resilience and sensitivity components, assuming that fish and phytoplankton do not respond similarly to environmental factors and that, consequently, there is no congruence between sensitivity and resilience patterns between of two groups. Also, we tested the hypotheses that species-rich assemblages show higher resilience and sensitivity in French lakes (H2); the highest values of resilience and sensitivity are related to phytoplankton (H3); and assemblages from natural lakes have higher resilience and sensitivity level (H4). We found similar resilience levels in spatially close fish assemblages due to fish dispersal limitations that contributed to create regional patterns in functional structure. Besides, acidity and eutrophication processes are good indicators of sensitivity level for fish. There is a mismatch in resilience and sensitivity levels between fish and phytoplankton, reinforcing importance of using a multi-taxa approach. Also, the components were positively related to taxonomic richness in assemblages showing importance of conserving biodiversity. Finally, we observed higher values of resilience and sensitivity for phytoplankton, as expected for a highly diverse group. Additionally, phytoplankton assemblages in natural lakes showed higher resilience levels than artificial environments, confirming the importance of preserving natural systems to conserve ecosystem functionality.